2022
DOI: 10.18805/bkap489
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Millet Starch

Abstract: The popularity of millet and its products is growing worldwide due to its health-promoting characteristics. The starch in millet is the most essential element, accounting for around 70% of total millet-grains and determining the quality of food items based on millets. The structural, functional and physicochemical features of starch determine its use for various purposes. Natural starch does not have the characteristics needed for specific purpose. Modifications in the structures of starch can be used to get p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Native starch is utilized as a texture stabilizer and conditioner in food systems. Still, its usage in industrial applications is limited due to its functionality as compared to the modified starch [ 26 , 49 ]. Native starch has some inherent properties such as instability to thermal, high hot-paste viscosity and shear stress, and a tendency to degrade rapidly in conjunction with low stability when kept in cold storage as well as weak resilience to acid, shear, and high temperatures, it is responsible for the deterioration of product quality and makes it less acceptable for widespread use in the food processing sector [ 99 ].…”
Section: Modification Approaches For Millet Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…Native starch is utilized as a texture stabilizer and conditioner in food systems. Still, its usage in industrial applications is limited due to its functionality as compared to the modified starch [ 26 , 49 ]. Native starch has some inherent properties such as instability to thermal, high hot-paste viscosity and shear stress, and a tendency to degrade rapidly in conjunction with low stability when kept in cold storage as well as weak resilience to acid, shear, and high temperatures, it is responsible for the deterioration of product quality and makes it less acceptable for widespread use in the food processing sector [ 99 ].…”
Section: Modification Approaches For Millet Starchmentioning
confidence: 99%
“…of starches [ 140 , 141 ]. Numerous researchers have reported that modifying approaches may help improve application starch functionality [ [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] ,…”
Section: Effects Of Modification Techniques On the Functional Propert...unclassified
“…The physicochemical and functional characteristics of starch define its desired function or involvement in a specific sector. Foxtail millet starch is greatly composed of amylose, which can be utilized for making resistant starch made products such as thickener, binder, flavor encapsulating agent, emulsion stabilizers, gelling agents, and so forth (Dimri & Singh, 2022). Being gluten free, they can serve as an excellent choice for people facing celiac disease.…”
Section: Modern Day Utilization Of Foxtail Millet (S Italica) In Food...mentioning
confidence: 99%
“…On the other hand, amylopectin possesses a significantly higher number of branches. The molecular structure of starch components is intricately linked to their production, the physical structures of granules, their functionality, and potential applications (Dimri & Singh, 2022) et al., 2016). The starch granules in FM starch are polygonal, less oval, and vary in size (He et al, 2015).…”
Section: Foxtail Millet Starchmentioning
confidence: 99%